Neonatal diphtheria - Oran, Olcay; Kanra, Güler; Gürses, Nuran (The Turkish Journal of Pediatrics, 1979)
C. xerosis has not been reported as a cause disease in man, therefore a case of neonatal diphtheria caused by nontoxigenic, virulent C.xerosis in a 27-day-old baby boy was reported.